2009
DOI: 10.1002/chem.200802652
|View full text |Cite
|
Sign up to set email alerts
|

Michael Additions versus Cycloaddition Condensations with Ethyl Nitroacetate and Electron‐Deficient Olefins

Abstract: Ethyl nitroacetate (1) reacts with electron-poor olefins in the presence of a base to give either the Michael adducts 3 or the isoxazoline cycloadducts 4, resulting from water elimination. The proportions of the two products depend on the reaction conditions and change in the course of the process. Kinetic profiles for the two reactions show that the cycloaddition-condensations require long induction times that dramatically decrease upon addition of a copper salt to the catalytic system: the drops in the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 97 publications
1
13
0
Order By: Relevance
“…* Heating the reaction mixture is favourable for the condensation reaction, particularly when this reaction is in competition with the conjugate addition. [31] This suggests that the release of the water is the rate-determining step and not the cycloaddition. However, at 100 8C the decomposition of nitroacetate is detrimental.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…* Heating the reaction mixture is favourable for the condensation reaction, particularly when this reaction is in competition with the conjugate addition. [31] This suggests that the release of the water is the rate-determining step and not the cycloaddition. However, at 100 8C the decomposition of nitroacetate is detrimental.…”
Section: Resultsmentioning
confidence: 98%
“…(2)]. [26][27][28][29][30][31] Whereas the former method requires anhydrous conditions and dehydrating reagents in stoichiometric amounts, [32,33] the latter condensation reaction in chloroform relies on the acid-catalysed deAbstract: Base-catalysed condensation reactions of nitroacetic esters with dipolarophiles to give isoxazole derivatives proceed faster, and often with higher yields, in the presence of water than in organic solvents such as chloroform. Kinetic profiles show that induction times are greatly reduced when the reaction is performed "in water" or "on water".…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that compounds containing electron‐deficient double bonds, on treatment with “active” primary nitro compounds (i.e., bearing an EWG geminal to the nitro group) in chloroform, undergo either cycloaddition/condensation to give isoxazole derivatives 2 or conjugate addition to yield 3 , depending on the catalyst employed and the Michael acceptor (Scheme ) 29…”
Section: Resultsmentioning
confidence: 99%
“…Nitroalkanes did not react under these conditions. However, we have previously shown that on addition of a Cu II salt to the base, the cycloaddition/condensation predominated in chloroform and not only active nitro compounds but also nitroalkanes underwent condensation selectively 29,30. Their reactions in various solvents with catalytic Cu II are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Nitro compounds with enhanced acidity and dipolarophiles condense to form the product by organocatalysis. [20][21][22][23] 1,4-Diazabicyclo[2.2.2]octane (DABCO) gives the best results if used alone, but the reaction becomes faster on addition of a Cu II salt. With a Cu II salt, other tertiary amines like triethylamine (TEA) or N-methylpiperidine (NMP) appear to be more suitable and cycloaddition/condensation reactions occur even with nitroalkanes.…”
Section: Introductionmentioning
confidence: 98%